P.040 Value-based approach to the management of Inflammatory Neuropathies: Incorporating objective outcome measures in clinical care. (June 2022) - Smith, CB; Chapman, K; Mezei, M; Beadon, K
Abstract : Background: Measuring outcomes that matter to patients is a key component of ensuring patient-centred care. In Chronic Inflammatory Neuropathies (CINs), where immunomodulatory treatments have risks and high costs, systematic evaluation of disease progression is needed to ensure patients are achieving outcomes that reflect their values and goals. The aim of this project is to evaluate the feasibility of objective outcome measure (OOM) use in the clinical setting. Methods: Prospective data was collected from 27 participants with CIDP or MMN. Participants completed and provided feedback on patient-reported outcome measures including quality of life, activity and participation, pain and fatigue, as well as grip strength, 9-hole peg test, 10 meter walk, muscle strength and sensation. Focus groups were conducted to collect qualitative data. Results: The majority of OOMs were considered relevant to 90% of participants. The top three ranked measures were muscle strength testing, daily activities questionnaire and quality of life questionnaire. 52% of participants identified balance and/or detailed gait assessment as an important factor that was not part of collected OOMs. Conclusions: OOMs allow for appropriate monitoring of patients and optimization of immunotherapy treatment. By tracking longitudinal results that matter to patients, patients can better participate in shared-decision making. Clinicians should adopt OOMs going forward.